A Hard Day for a Hangover - Jones, Darynda (New York : St. Martins Press, 2022)
" Some people greet the day with open arms. Sheriff Sunshine Vicram would rather give it a hearty shove and get back into bed, because theres just too much going on right now. Theres a series of women going missing, and Sunny feels powerless to stop it. Theres her persistent and awesomely-rebellious daughter Auri, whos out to singlehandedly become Del Sols youngest and fiercest investigator. And then theres drama with Levi Ravinder- the guy shes loved and lusted after for years. The guy who might just be her one and only. The guy who comes from a family of disingenuous vipers looking to oust him-and Sunshine-for good. Like we said, the new day can take a hike."--
Keywords: Policewomen -- Fiction; Sheriffs -- Fiction; Detective and mystery fiction; Humorous fiction